2013
DOI: 10.1371/journal.pone.0077936
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Circulating MicroRNA Expression in Experimental Sepsis Using Cecal Ligation and Puncture

Abstract: The levels of circulating microRNAs (miRNAs) in mice with experimental sepsis induced by cecal ligation and puncture (CLP) were determined using whole blood samples obtained from C57BL/6 mice at 4, 8, and 24 h after CLP; miRNA expression analysis was performed in these samples using an miRNA array. Microarray analysis revealed upregulation of 10 miRNA targets (miR-16, miR-17, miR-20a, miR-20b, miR-26a, miR-26b, miR-106a, miR-106b, miR-195, and miR-451). The expression of these miRNA targets in the whole blood,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 49 publications
1
40
1
Order By: Relevance
“…These miRNAs are preserved in circulation and are quantifiable, which supports the potential role as diagnostic or progression biomarkers in various diseases [13,24,25]. These miRNAs are preserved in circulation and are quantifiable, which supports the potential role as diagnostic or progression biomarkers in various diseases [13,24,25].…”
Section: Discussionmentioning
confidence: 53%
“…These miRNAs are preserved in circulation and are quantifiable, which supports the potential role as diagnostic or progression biomarkers in various diseases [13,24,25]. These miRNAs are preserved in circulation and are quantifiable, which supports the potential role as diagnostic or progression biomarkers in various diseases [13,24,25].…”
Section: Discussionmentioning
confidence: 53%
“…Exosomes were separated from the sera of all participants using ExoQuick precipitation (System Biosciences Inc., Palo Alto, CA, USA) according to the manufacturer instructions [13,14].…”
Section: Precipitation Of Serum Exosomesmentioning
confidence: 99%
“…miR-16 is also a universal reference gene because of its high expression level. But some recent studies reported up-regulation of miR-16 in plasma in some diseases, such as autoimmune thyroid disease [26], experimental sepsis [27] and gastric cancer [28]. Other research demonstrated that miR-16 is highly expressed in red blood cells so that any hemolysis of blood samples strongly affects their level in plasma [29].…”
Section: Figurementioning
confidence: 99%